1989
DOI: 10.2307/3577713
|View full text |Cite
|
Sign up to set email alerts
|

Radioresistance Induced by Oncogenic Transformation

Abstract: Rat embryo cells at various stages of oncogenic transformation are obtained by a combination of X irradiation and transfection with the ras and the myc oncogenes. Transfection with either the ras or the myc oncogenes can lead to increased radioresistance, relative to the parental cells. X-ray-transformed clones of the transfected cells do not show additional alteration in radioresponse. Incorporation of the two oncogenes appears to lead to a higher degree of radioresistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…We and others have shown that transfection of rodent fibroblast cell lines with mutant H-Ras, N-Ras, and K-Ras results in decreased radiosensitivity (14,(50)(51)(52)(53) and that, conversely, loss of mutant K-ras alleles from DLD-1 human colon carcinoma or N-ras alleles from human HT1080 sarcoma cells leads to increased radiosensitivity (13). However, other studies have shown that transfection of Rat2 Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that transfection of rodent fibroblast cell lines with mutant H-Ras, N-Ras, and K-Ras results in decreased radiosensitivity (14,(50)(51)(52)(53) and that, conversely, loss of mutant K-ras alleles from DLD-1 human colon carcinoma or N-ras alleles from human HT1080 sarcoma cells leads to increased radiosensitivity (13). However, other studies have shown that transfection of Rat2 Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Primers were designed to amplify the promoter CpG-rich region of PTEN, HIN1, RASSF1A, and RASSF2A gene by Methprimer. 6 The sequences of the primers are listed in Supplementary Table S1. All PCR reactions were done on PTC-100 thermocyclers (MJ Research) in a final volume of 25 AL containing bisulfite-modified DNA (2 AL), 1Â PCR buffer, 1.5 mmol/L MgCl 2 , 0.2 mmol/L deoxynucleotide triphosphate, 10 pmol of each primer, and 1 unit of Thermostar polymerase (ABgene).…”
Section: Methodsmentioning
confidence: 99%
“…It was initially shown that the resistance of NIH3T3 cells to radiation could be enhanced by the expression of an activated H-Ras gene (2). This was later confirmed independently by several other groups using rodent cells, including rat embryo fibroblasts and rat rhabdomyosarcomas (3)(4)(5)(6), and human tumor cells, including an EJ Ras-transformed bladder carcinoma, DLD-1 colon carcinoma, and HT1080 fibrosarcoma (7,8). In agreement with such Ras-mediated radioresistance, several groups have reported that the blocking of Ras activity leads to an increase in radiosensitivity.…”
Section: Introductionmentioning
confidence: 62%
“…Oncogenic H-Ras has been shown to confer radioresistance to the majority of cell types examined (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). To identify the potential oncogenic H-Ras target genes that might be involved in the oncogenic H-Ras-mediated increased radioresistance, the effect of oncogenic H-Ras on the g-ray-induced cytotoxicity was initially reevaluated in the NIH3T3 cells.…”
Section: Resultsmentioning
confidence: 99%